represión al Magisterio y a las mujeres en la Ribera estellesa de Navarra (1936-1939) - Martínez Aznal, Rubén (Huarte de San Juan. Geografía e Historia, 2015)
The fascist repression during the Spanish Civil War severely affected two of most vulnerable social sectors, teachers and women. Purging teachers was carried out by behavior reports and the authority in charge of doing this was the Education Supreme Council. The purging to women was done consciously and deliberately and had a specific ceremonial in which women were expected to be humiliated publicly. Shaving heads, torture and castor oil were the most commonly used methods. Navarra, which led the Uprising from the beginning, shows two different sides given the high number of victims of fascist repression invites us to consider that the Republic settled in Navarre in a larger extent than it’s usually admitted.
Keywords: Repression; teachers; women; spanish civil war; ribera estellesa; Navarra